Severe Type 1 Thumb Boutonniere Deformity with Interphalangeal Joint Dislocation in a Young Patient: A Case Report - Sarthak Aggarwal; Jeffrey G Stepan (Journal of Orthopaedic Case Reports)
Introduction: Thumb boutonniere deformity, commonly associated with autoimmune arthropathies, presents as metacarpophalangeal (MCP) joint flexion and interphalangeal (IP) joint hyperextension. Literature guiding management remains incomplete and out-of-date, and it largely addresses low-demand populations. IP joint dislocation is a particularly severe presentation that notably has only been reported once before. Case Report: We report a rare case of severe Type 1 thumb boutonniere deformity with IP joint dislocation in a 42-year-old, high-demand female patient with a history of autoimmune diseases. We describe the successful treatment of this severe thumb deformity using MCP arthrodesis and temporary IP joint pinning, which resulted in preserved function and stability. At 1-year follow-up, the patient reported good function of the thumb with no instances of IP joint dislocation. Conclusion: In prior literature, MCP arthroplasty with IP arthrodesis has been recommended in severe thumb boutonniere deformities, but this may be inappropriate for younger, higher-demand patients. Surgeons should obtain a comprehensive understanding of each patient’s anatomy and functional goals to best develop treatment strategies. The success of MCP arthrodesis and temporary IP joint pinning in this population is evidenced by the maintained IP joint range of motion and lack of dislocation with pinch and grip activities at 1 year follow-up.